Evaluating IT Governance Structure Implementation in the Gulf Cooperation Council Region. (February 2020) - Nicho, Mathew; Muamaar, Suadad
Abstract: IT governance (ITG) implementations in organizations started to gain momentum during the turn of the twenty first century mainly due to (but not limited to) the need for IT business alignment, better return of investment, effective utilization of IT and for a strategic direction of IT. This initially mandates to establish and implement a set of ITG structures in the organization to initiate, adopt, and implement relevant ITG frameworks to set in the motion of successful ITG implementation. While researchers have stated twelve relevant ITG structures that needs to be set in place, two questions remain in terms of the two factors namely 'ease of implementation/use' and 'effectiveness' of these ITG structures. With scant research in this domain, we explore the relationship of these two factors on the twelve ITG structures through a survey of senior managers involved in ITG domain in the Gulf Cooperation Council (GCC) region. With diverse board and executive level cultures evident in different regions of the world, the adoption of these ITG frameworks and standards depend on the ITG practices being followed in each cultural context. The results thus assist organisations and ITG consultants in the GCC region to know the level of effectiveness of relevant ITG structures as well as the implementation effort required for these.